15.3k views
5 votes
Which expression is equivalent to [(3xy^-5)^3/(x^-2y^2)^-4]^-2?

a. x^10y^14/729
b. x^22/18y^46
c. 729/x^10y^14
d. 18y^46/x^22

2 Answers

0 votes

Answer: A

Explanation:

built different

User Naugler
by
5.8k points
2 votes

Answer:- a.The given expression is equivalent to
(x^(10)y^(14))/(729)



Given expression:-
[((3xy^(-5))^3)/((x^(-2)y^2)^(-4))]^(-2)


=[((3)^3x^3y^(-5*3))/(x^(-2*-4)y^(2*-4))]^(-2).........(a^m)^n=a^(mn)


=[(27x^3y^(-15))/(x^8y^(-8))]^(-2)


=[27x^(3-8)y^(-15-(-8))]^(-2)............(a^m)/(a^n)=a^(m-n)


=[27x^(-5)y^(-7)]^(-2)=(27)^(-2)(x^(-5))^(-2)(y^(-7))^(-2).........(a^m)^n=a^(mn)


=(1)/((27)^2)(x^(10)y^(14))=(x^(10)y^(14))/(729)

Thus a. is the right answer.


User Jack Dsilva
by
6.0k points